Lessons on Peruvian wart or "Carrion Disease" - Arce, Julián (1918)
Peruvian wart is, inoculable man and animals, limited to certain areas of Peru geographical distribution and is characterized by the following two anatomo-clinical sindromas infectious disease: 1 anemia, which may be simple, in some cases (benign wart), or acute and pernicious in other (malignant wart); and 2nd outbreak, more or less abundant, of granulomatous tumors, very vascular, known by the misnomer of warts. The transmission of this disease is made, probably through a blood-sucking insect.